Thinking outside the skin: Look at the thyroid for true diagnosis - Fatemi Naeini, Farahnaz; Abtahi Naeini, Bahareh; Sadeghiyan, Hamidreza; Pourazizi, Mohsen (Archives of Advances in Biosciences, 2015)
Keratoderma is a group of disorders characterized by abnormal thickening of skin. Acquired palmar keratoderma has many underlying causes. The association of thyroid disease and palmar keratoderma rarely reported. Hypothyroidism, although very rare association, must be suspected in patients with acquired PPK, particularly when it occurs in setting of systemic symptoms or predisposing conditions.We report first case of acquired plantar keratoderma associated with undiagnosed hypothyroidism in Down syndrome.